Nomina Berelasi Air yang Dihasilkan Entitas Dalam Bahasa Bali - Carma Citrawati, Dewa Ayu; Sudipa, I Nengah; Suryati, Ni Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 25 No 1 (2018): MaretDO - 10.24843/ling.2018.v25.i01.p08, 2018)
This Research aim at finding nouns related to water in Balinese langage, particulary lexicon that belong to entity of human, flora, and fauna. Lexicon with noun category are analyzed using Natural Semantics Metalanguage (NSM). The data in form of oral speech spoken by native speaker of Balinese were collected from two regency, Buleleng and Klungkung. The method used to collect data is the observing method and skill method. Data analyzed by identity and distributional method. The result of data analysis is presented by using formal and informal method. The result shows that the semantic structure of noun related to water portray various structure. There are 13 nouns related to the water from three entity of human, flora, and fauna, i.e peluh, enceh, téngés, yéh cunguh, poos, tétéh, yéh mata, yéh nyonyo and banyeh. these nouns are compared to semantic prime of SOMETHING-THING which has polysemy meaning with semantic prime of PEOPLE. These nouns affect their entities positively and negatively.